In too deep : BP and the drilling race that took it down - Reed, Stanley, 1950-; Fitzgerald, Alison (Hoboken, N.J. : Bloomberg Press, 2011)
"The truth behind the greatest environmental disaster in U.S. history In 2005, fifteen workers were killed when BP's Texas City Refinery exploded. In 2006, corroded pipes owned by BP led to an oil spill in Alaska. Now, in 2010, eleven BP workers were killed in the Gulf of Mexico's Macondo blowout. What's next? In In Too Deep: BP and the Drilling Race that Took It Down, Stanley Reed--a journalist who has covered BP for over a decade--and investigative reporter Alison Fitzgerald answer not only the question of what's next but also examine why these disasters always happen to BP and not to the other large oil companies. The book: Shows that practices put in place by former BP CEO John Browne who was forced to resign after salacious details of his private life emerged in 2007 may have more to do with the disaster than anything Details a BP built on risk-taking and cost-cutting Examines the past, present, and future of BP In August 2010, BP successfully "killed" the company's damaged deepwater well. But, the environmental fallout and public relations campaign to rebuild the brand are just beginning. In Too Deep details why BP suffered this disaster, why now, and what's next for the oil giant."--Provided by publisher.
Night of horror, day of triumph -- The oil lord -- Agents of empire -- The big kahuna of the gulf -- Money, politics, and bad timing -- Lord Browne's long goodbye -- Riding the throughput curve -- Tony Hayward comes up short -- Disaster on the Horizon -- BP struggles to survive.
Includes bibliographical references and index.
Keywords: BP (Firm); BP Deepwater Horizon Explosion and Oil Spill, 2010.; Oil wells -- America, Gulf of -- Blowouts